Organization of primary health care of children second professional: qualitative research - Alexandre, Ana Maria Cosvoski; Bicudo, Daniele de Oliveira; Fernandes, Ana Paula Pereira; de Souza, Claudia; Maftum, Mariluci Alves; Mazza, Verônica de Azevedo (Online Brazilian Journal of Nursing, 2010)
Abstract: Descriptive qualitative research study were held aiming to apprehend health professionals’ perception on child health care organization and practices in the context of the Family Health Strategy Program. Carried out in three health units in the municipality of Curitiba, Paraná State/Brazil from March to June/2008. Semi-structured interviews Three health professionals per category (doctors, nurses, nursing technicians/aides and community health agents) were the subjects. The analyzed data were organized in the following categories: Care model; Coverage area; Workforce; Family needs toward child development. It was evidenced that health unit facilities do not meet the change proposal in the health care model. Teamwork stands out as a facilitator in care delivery. Health professionals point out failures in reference system as well as day care shortage. It is evidenced family blaming for their children’s health. It is considered that there must be a process of change in the prevailing care model into one which effects health promotion, investments in infrastructure are also required, professional qualification, and also public policies which guarantee care integrality and better articulation among the different sectors of society aiming to family strengthening toward child development.